The Effect of Different Dietary Sugars on the Development and Fecundity of Harmonia axyridis - Li, Yan; Wang, Shasha; Liu, Yongkang; Lu, Yuting; Zhou, Min; Wang, Su; Wang, Shigui (Frontiers in Physiology, 2020)
The aim of this study was to screen synergistic substances included in existing artificial feeds in order to improve the fertility and survival rate of Harmonia axyridis (Pallas) (Coleoptera: Coccinellidae), an efficient pest predator. To this end, we analyzed the potential effects of glucose and trehalose on the growth, development, and reproduction of H. axyridis and evaluated the effect of three different artificial feeds on the energy stress of H. axyridis. The artificial diets contained fresh pork liver, honey, sucrose, vitamin C, and royal jelly, which was marked it as Diet1. The glucose was added to diet1, which was marked it as diet2, while adding trehalose to diet1 was marked as diet3. The pre-oviposition period of H. axyridis on Diet 1 was slower than that of Diet 2 and Diet 3. Additionally, the spawning quantity and incubation rate of insects on Diet 2 and Diet 3 were significantly higher than that of those on Diet 1. Finally, the larval developmental time on Diet 1 was significantly slower than that of Diet 2 and Diet 3. These results indicate that the addition of an appropriate amount of glucose or trehalose may affect positively the growth, development, and reproduction of H. axyridis. In addition, further studies showed that ATP, amino acids and fatty acids content in the H. axyridis also increased after the addition of the synergistic substance. All these results show that proper adjustment of stored energy anabolic and catabolism is important to maintain the metabolic balance of the insect’s entire life cycle and the addition of glucose or trehalose has a certain effect on the life indicators of H. axyridis.